GLP-1 receptor agonists and cardiovascular outcomes in patients with type 2 diabetes: Clinical evidence and best practice. Issue 2 (February 2022) - Coke, Lola A.; Deedwania, Prakash C.; Hinnen, Debbie; Magwire, Melissa; Miller, Nancy H.
ABSTRACT: Cardiovascular disease (CVD) is a major cause of death and disability among people with type 2 diabetes (T2D), presenting a significant impact on longevity, patient quality of life, and health care costs. In the United States, attainment of recommended glycemic targets is low and T2D-related cardiovascular complications remain a significant burden. Many glucose-lowering treatment options are available, but glucagon-like peptide-1 receptor agonists (GLP-1RAs) and sodium-glucose cotransporter-2 (SGLT-2) inhibitors are recommended in recent guidelines as the preferred add-on therapy to metformin to improve glycemic control. This is particularly the case for patients with T2D and established atherosclerotic CVD, at high risk of atherosclerotic CVD, and/or with chronic kidney disease. Recommendations were based on GLP-1RA and SGLT-2 inhibitor cardiovascular outcomes trials (CVOTs), which consistently showed that these agents pose no additional cardiovascular risk compared with placebo. Three GLP-1RAs (liraglutide, dulaglutide, and subcutaneous semaglutide) demonstrated significantly lower major adverse cardiovascular events versus placebo and are now approved for this indication. However, to realize improvement in outcomes in the clinical setting, organized, systematic, and coordinated approaches to patient management are also needed. For example, nurse-led diabetes self-management education and support programs have been shown to be effective. This article explores T2D management with emphasis on cardiovascular risk and CVOTs performed to date and reviews the clinical experience with GLP-1RAs for managing hyperglycemia and their impact on cardiovascular risk. In addition, practical guidance is given for key health care providers involved in the care of patients with T2D with cardiovascular risk outside of diabetes clinics/endocrinology centers.